Community Preparedness of Vulnerable Groups and Non-Vulnerable Groups for Landslides in Kalirejo village, Salaman District, Magelang Regency (Jurnal Penelitian dan Pengembangan Kesehatan Masyarakat Indonesia, 2022)
Disaster preparedness is a series of activities carried out to anticipate disasters through organizing and through appropriate and efficient steps. Disaster preparedness in handling landslides needs to be built and improved because the disaster preparedness vulnerable and non-vulnerable groups. The research method used is descriptive quantitative by using analytic observational study and using cross sectional method. The total sample of the study was 102 respondents consisting of 28 vulnerable groups and 74 non-vulnerable groups. The result of the study showed that landslide’s disaster preparedness for vulnerable groups was included in the unprepared category, while landslide’s disaster preparedness for the non-vulnerable group was included in the almost ready category.